A Trust Region Algorithm for Constrained Nonsmooth Optimization Problems (Journal of Computational Mathematics, 2001)
This paper presents a new inexact trust region algorithm for solving constrained nonsmooth optimization problems. Under certain conditions, we prove that the algorithm is globally convergent.
Keywords: Trust region method; Nonsmooth function; Constrained optimization; Global convergence.